Composite strengthening method for improving strength of flexible glass
By using ultrafast laser on flexible glass for surface microcrystalization, combined with chemical strengthening technology, the problem of insufficient strength of ultrathin flexible glass is solved, and its strength and safety is improved, which is suitable for the high-strength needs of ultrathin glass.
Patent Information
- Application Number
- CN202411855832.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During use, ultra-thin flexible glass is prone to insufficient strength due to insufficient surface microcracks and insufficient chemical strengthening of low-temperature molten salts, and has low service life and safety.
Ultrafast laser is used to carry out full-surface thermal accumulation treatment, activate microcrystalization of the glass surface, and then undergo chemical reinforcement treatment. By adjusting laser parameters and chemical reinforcement conditions, the strength and bending performance of the glass are improved.
It effectively overcomes the deformation problems caused by traditional physical tempering and the insufficient strength caused by single chemical reinforcement, improves the strength and safety of flexible glass, while maintaining its ultra-thin characteristics and optical properties.
Smart Images

Figure CN119874215A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass, and in particular to a composite strengthening method for improving the strength of flexible glass. Background Art
[0002] The development of smart electronic products and curved display technologies, such as foldable smartphones and bendable electronic wearables, has put forward higher requirements for flexible displays. Flexible glass (UTG) refers to ultra-thin glass with a thickness of ≤0.1mm. It is the core material of foldable display devices and has the characteristics of ultra-thinness, wear resistance, high strength, and bendability. However, as display terminal products develop towards ultra-thinness, the thickness of flexible cover plates is also gradually developing towards ultra-thinness. However, the ultra-thinness of glass will amplify the adverse effects of defects on glass strength. Surface microcracks are inevitably present on the surface of ultra-thin glass. Under service conditions, the fracture toughness and the pre-applied compressive stress on the surface of the glass begin to expand. When the cracks reach the tensile stress layer, the glass breaks. At this time, the residual stress of the glass is instantly released, and the glass quickly breaks into countless pieces, seriously affecting the safety and durability of the product. Therefore, high strengthening of ultra-thin flexible glass cover plates is particularly important.
[0003] There are two main methods of glass strengthening: physical strengthening and chemical strengthening. Physical strengthening is to heat the glass twice to above the sag temperature and below the softening temperature, and then rapidly cool it in a cooling medium to produce compressive stress on the glass surface. However, the overall heating of thin glass during physical strengthening will produce inherent deformation problems, which limits its application in the field of ultra-thin glass strengthening. Chemical strengthening, also known as ion exchange, is to exchange small-radius alkali metal ions in the glass surface structure with large-radius alkali metal ions in high-temperature molten salts to produce compressive stress on the glass surface, thereby improving strength. The temperature required for chemical strengthening is relatively low, only about 400°C, and the internal tensile stress of the glass after ion exchange is small, and the related optical properties have not changed. Compared with physical strengthening, it is more suitable for strengthening ultra-thin glass. However, the extremely thin flexible glass is affected by the production process and equipment, which will multiply the defects on the glass surface. The microcracks on its surface have a great influence on the strength of the glass compared to thick glass. Once the degree of ion exchange is insufficient, it is easy to break into sharp fragments under the action of external forces, and the service life and safety will be greatly reduced. Summary of the invention
[0004] In order to solve the deficiencies in the prior art, the present invention provides a composite strengthening method for improving the strength of flexible glass, aiming to improve the strength and safety of flexible glass.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A composite strengthening method for improving the strength of flexible glass includes a flexible glass cover plate, wherein the thickness of the glass substrate is between 10 and 100 μm, and the composite strengthening steps of the flexible glass cover plate are as follows:
[0007] The first step is to clean and dry the surface of the flexible glass cover plate prepared on the production line;
[0008] In the second step, ultrafast laser is used to perform full-surface heat accumulation treatment on the front and back sides of the flexible glass, and natural cooling is used to make the upper and lower shallow surfaces of the glass microcrystallized;
[0009] The third step is to preheat the flexible glass cover plate after the laser treatment in the previous step;
[0010] The fourth step is to immerse the preheated flexible glass cover into molten salt for chemical strengthening treatment;
[0011] Step 5, annealing the flexible glass cover after chemical strengthening treatment;
[0012] The sixth step is to clean and dry the molten salt on the flexible glass cover after annealing.
[0013] As a further solution of the present invention: the component range of the flexible glass is: SiO2: 58-64, Al2O3: 12-20, Na2O: 11-15, K2O: 3-6, CaO: 2-4, MgO: 2-6, ZrO2: 0.2-1.5, Li2O: 0-1.2.
[0014] As a further solution of the present invention: the ultrafast laser is a linear pulse laser with a pulse width of 230fs-6ps, a laser scanning speed of 10μm / s-200μm / s, a laser repetition frequency of 200KHz-800KHz, and a laser wavelength of 780nm-1000nm.
[0015] As a further solution of the present invention: the molten salt used for chemical strengthening is KNO3 or a mixture of NaNO3 and KNO3, and the mixing ratio is KNO3 / NaNO3: 0.1-10.
[0016] As a further solution of the present invention: the preheating temperature of the flexible glass cover is 300-500°C, the preheating temperature of the molten salt is 300-600°C, the chemical strengthening time is 5-180 minutes, and the annealing temperature is 50-150°C.
[0017] As a further solution of the present invention: when the glass thickness is 10-30 nm, only one chemical strengthening treatment is required, and when the glass thickness is 30-100 nm, two chemical strengthening treatments are required.
[0018] Beneficial effects of the present invention:
[0019] Glass, as an amorphous material, is a substance produced by preventing the melt from crystallizing during the cooling process by means of rapid cooling. One of its most important characteristics is metastability, that is, during the transformation from melt to glass, due to the rapid increase in the viscosity of the melt, the atoms or ions inside do not have time to arrange in order to form crystals, and the latent heat of crystallization cannot be released. Therefore, glass materials generally have higher internal energy, and its energy is between that of the melt and the crystal. The present invention strengthens ultra-thin flexible glass. In order to solve the problem that traditional thermal tempering behavior is not suitable for ultra-thin glass, the local thermal effect is introduced by using ultrafast lasers to relax the glass network structure in the target area, thereby overcoming the potential barriers required for lattice formation, activating the particles in the glass, and causing them to rearrange, realizing the transformation of microcrystals on the glass surface, and the depth and intensity of glass strengthening can be adjusted by adjusting the pulse width, scanning speed, repetition frequency, laser wavelength, etc. of the pulsed laser.
[0020] The flexible glass cover is strengthened by adopting the above steps, and laser-induced glass surface microcrystallization is used before chemical strengthening, which solves the inherent deformation and warping problems caused by traditional physical tempering, as well as the insufficient strength of the flexible glass caused by insufficient degree of ion exchange in single chemical strengthening. While ensuring the appearance of ultra-thin flexible glass, it can also ensure the strength and bending performance of the glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The present invention will be further described below in conjunction with the accompanying drawings.
[0022] Figure 1 A schematic diagram of the compressive stress distribution structure on the surface of the flexible glass cover after composite strengthening in an embodiment of the present invention is shown. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Embodiment 1
[0025] See also Figure 1 As shown, the present invention is a composite strengthening method for improving the strength of flexible glass, comprising the following steps:
[0026] Step 1: Cut the flexible glass cover plate prepared on the production line into glass samples with a size of 140 mm*70 mm and a thickness of 30 um, and then clean them by ultrasonic cleaning and dry them;
[0027] Step 2: Use a linear femtosecond laser to scan the entire surface of the flexible glass, with a pulse width of 30fs, a laser scanning speed of 200μm / s, a laser repetition frequency of 450KHz, and a laser wavelength of 800nm; after scanning, a local heat accumulation effect is generated on the upper and lower surfaces of the glass, element migration and chemical bond breaking and recombination occur in the molten area, and the upper and lower shallow surfaces of the glass are microcrystallized by natural cooling;
[0028] Step 3: insert the flexible glass cover plate treated by laser in the previous step into the strengthening rack, perform preheating at 400°C for 0.5h, and heat the molten salt with a mixing ratio of KNO3 / NaNO3=0.25 to 420°C to make it completely melted and clarified uniformly;
[0029] Step 4: quickly insert the preheated glass piece into the molten salt that has been uniformly melted for chemical strengthening, keep the temperature at 420°C for 30 minutes, and then take out the sample;
[0030] Step 5: Place the glass sheet together with the strengthening rack into a muffle furnace at 100° C. for annealing for 1 hour. Finally, wash the molten salt on the flexible glass cover with running water and dry it in a drying oven to obtain sample I.
[0031] Embodiment 2
[0032] Step 1: Cut the flexible glass cover plate prepared on the production line into glass samples with a size of 140 mm*70 mm and a thickness of 30 um, and then clean them by ultrasonic cleaning and dry them;
[0033] Step 2: insert the cleaned flexible glass cover plate into the strengthening rack, perform a preheating treatment at 400°C for 0.5h, and heat the molten salt with a mixing ratio of KNO3 / NaNO3=0.25 to 420°C to make it completely melted and clarified uniformly;
[0034] Step 3: quickly insert the preheated glass piece into the molten salt that has been uniformly melted for chemical strengthening, keep the temperature at 420°C for 30 minutes, and then take out the sample;
[0035] Step 4: Place the glass sheet together with the strengthening rack in a muffle furnace at 100°C for 1 hour for annealing, and finally clean the molten salt on the flexible glass cover with running water and place it in a drying oven for drying;
[0036] Step 5: preheat the dried glass sheet for 0.5h at 400°C, and heat the molten salt with a mixing ratio of KNO3 / NaNO3=4 to 420°C to make it completely melted and clarified uniformly;
[0037] Step 6: quickly insert the preheated glass piece into the molten salt that has been uniformly melted for secondary chemical strengthening. Keep the temperature at 420°C for 10 minutes and then take out the sample.
[0038] Step seven, put the glass sheet after secondary chemical strengthening together with the strengthening frame into a muffle furnace at 100° C. for annealing for 1 hour, and finally clean the molten salt on the flexible glass cover plate with running water, and put it into a drying oven for drying to obtain sample II.
[0039] Embodiment 3
[0040] Step 1: Cut the flexible glass cover plate prepared by the production line into glass samples with a size of 140mm*70mm and a thickness of 100um, and then clean them by ultrasonic cleaning and dry them;
[0041] Step 2: Use a linear femtosecond laser to scan the entire surface of the flexible glass, with a pulse width of 10fs, a laser scanning speed of 200μm / s, a laser repetition frequency of 400KHz, and a laser wavelength of 980nm. After scanning, a local heat accumulation effect is generated on the upper and lower surfaces of the glass, element migration and chemical bond breaking and recombination occur in the molten area, and the upper and lower shallow surfaces of the glass are microcrystallized by natural cooling.
[0042] Step 3: insert the flexible glass cover plate treated by laser in the previous step into the strengthening rack, perform preheating at 400°C for 0.5h, and heat the molten salt with a mixing ratio of KNO3 / NaNO3=0.25 to 420°C to make it completely melted and clarified uniformly;
[0043] Step 4: quickly insert the preheated glass piece into the molten salt that has been uniformly melted for chemical strengthening, keep the temperature at 420°C for 30 minutes, and then take out the sample;
[0044] Step 5: Place the glass sheet together with the strengthening rack in a muffle furnace at 100°C for 1 hour for annealing, and finally clean the molten salt on the flexible glass cover with running water and place it in a drying oven for drying;
[0045] Step 6: preheat the dried glass sheet for 0.5h at 400°C, and heat the molten salt with a mixing ratio of KNO3 / NaNO3=4 to 420°C to make it completely melted and clarified uniformly;
[0046] Step 7: quickly insert the preheated glass piece into the molten salt that has been uniformly melted for secondary chemical strengthening. Keep the temperature at 420°C for 30 minutes and then take out the sample.
[0047] Step eight, put the glass sheet after secondary chemical strengthening together with the strengthening frame into a muffle furnace at 100° C. for annealing for 1 hour, and finally clean the molten salt on the flexible glass cover plate with running water, and put it into a drying oven for drying to obtain sample III.
[0048] from Figure 1 It can be seen that due to the different thicknesses of the original sheets of Sample I and Sample III, the embodiment adopts one-time chemical strengthening and two-time chemical strengthening respectively in the chemical strengthening step as appropriate. The surface compressive stress and strengthening stress depth of the strengthened glass are both high, and it has excellent drop resistance. At the same time, compared with Sample II, the flexible glass of Sample I and Sample III is crystallized by femtosecond laser thermal excitation, and then chemically strengthened. The ion exchange efficiency is high during the chemical strengthening process, which is more conducive to improving the compressive stress and strengthening stress depth of the glass surface, and can reduce the change rate of the compressive stress value, better resist the central tensile stress and crack expansion, and ensure the appearance of the ultra-thin flexible glass while ensuring the strength and bending performance of the glass.
[0049] Sample II did not undergo femtosecond laser thermal excitation, but only underwent secondary chemical strengthening. The rate of change of the surface compressive stress value was too large, which could easily cause warping of the flexible glass and surface unevenness. If only chemical strengthening was performed once, the surface compressive stress value would be too low and the degree of tempering would be insufficient.
[0050] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A composite strengthening method for improving the strength of flexible glass, comprising a flexible glass cover plate, wherein the thickness of the glass substrate is between 10 and 100 um, characterized in that: The composite strengthening steps of the flexible glass cover are as follows: The first step is to clean and dry the surface of the flexible glass cover plate prepared on the production line; In the second step, ultrafast laser is used to perform full-surface heat accumulation treatment on the front and back of the flexible glass, and natural cooling is used to make the upper and lower shallow surfaces of the glass microcrystallized; The third step is to preheat the flexible glass cover plate after the laser treatment in the previous step; The fourth step is to immerse the preheated flexible glass cover into molten salt for chemical strengthening treatment; Step 5, annealing the flexible glass cover after chemical strengthening treatment; The sixth step is to clean and dry the molten salt on the flexible glass cover after annealing.
2. A composite strengthening method for improving the strength of flexible glass according to claim 1, characterized in that: The flexible glass composition range is: SiO2: 58-64, Al2O3: 12-20, Na2O: 11-15, K2O: 3-6, CaO: 2-4, MgO: 2-6, ZrO2: 0.2-1.5, Li2O: 0-1.
2.
3. A composite strengthening method for improving the strength of flexible glass according to claim 1, characterized in that: The ultrafast laser is a linear pulse laser with a pulse width of 230fs-6ps, a laser scanning speed of 10μm / s-200μm / s, a laser repetition frequency of 200KHz-800KHz, and a laser wavelength of 780nm-1000nm.
4. A composite strengthening method for improving the strength of flexible glass according to claim 1, characterized in that: The molten salt used for the chemical strengthening is KNO3 or a mixture of NaNO3 and KNO3, and the mixing ratio is KNO3 / NaNO3: 0.1-10.
5. A composite strengthening method for improving the strength of flexible glass according to claim 1, characterized in that: The preheating temperature of the flexible glass cover is 300-500°C, the preheating temperature of the molten salt is 300-600°C, the chemical strengthening time is 5-180 minutes, and the annealing temperature is 50-150°C.
6. A composite strengthening method for improving the strength of flexible glass according to claim 1, characterized in that: When the glass thickness is 10-30 nm, only one chemical strengthening treatment is required. When the glass thickness is 30-100 nm, two chemical strengthening treatments are required.
Citation Information
Patent Citations
Glass toughening method and toughened glass
CN108298826A
Chemical strengthening method for improving falling resistance and surface hardness of glass
CN111348841A
Microcrystalline glass cover plate, flexible screen assembly, electronic equipment and processing method of microcrystalline glass cover plate
CN111393032A
Preparation method of high-strength antibacterial flexible glass
CN115818981A
Glass and preparation method thereof, glass piece and preparation method thereof, and electronic equipment
CN115818982A